ANALISIS HUBUNGAN WORK INTERFERENCE WITH FAMILY TERHADAP BURNOUT PERAWAT WANITA DI RSUD Dr. R. GOETENG TAROENADIBRATA PURBALINGGA - Susanti, Indri Heri; Kurniawan, Wasis Eko (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
As a married worker, a female nurse is required to perform two roles at once, there are the role of wife and mother at home and as a working woman at the hospital. These assertion can lead to a collision between the responsibilities of their work at home and at the hospital. This situation can make a female nurse feel guilty and under pressure then leads them into burnout. The purposes of this study is to analyze the relationship between work interference with family with the female nurse’s burnout in RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. This is an analytic survey research using cross sectional method. The sample are 122 female nurses who have married in RSUD Dr. R. Goeteng Taroenadibrata Purbalingga, using total sampling technique. This study using bivariate analysis with Lamda test. The results showed there was a relationship between work interference with family with emotional exhaution of female nurses with p value 0,230; there is a relationship between work interference with family with depersonalization of female nurses with p value 0,127; and there is a relationship between work interference with family with decreased of personal acomplishment of female nurse with p value 0.725. Keywords: work interference with family, burnout, female nurses